Negative opinion on work as variable of career shift among doctors in Poland. Are we running out of doctors in post-COVID times? - Pruszyński, Jacek; Cianciara, Dorota; Engel, Janusz; Zgliczyński, Wojciech (Journal of Education, Health and Sport, 2022)
Introduction and objective. Work conditions and evaluation, stress, professional burnout among doctors are the subject of analyzes and research in Poland. Less attention is focused on the problem of leaving the profession. The aim of the study was to determine the relationship between the socio-demographic and professional characteristics of doctors and the subjective assessment of their current work and the willingness to undertake an alternative career. Material and methods. A survey was conducted among 315 doctors attending courses at the Medical Center of Postgraduate Education in 2018/19. The questionnaire consisted of 14 questions. The dependent variable was the declaration of willingness to change the medical profession to another, if it was possible to maintain income. The explanatory variables were socio-demographic and professional characteristics: gender, age and the performance of surgical and non-surgical specialties as well as subjective assessment of current professional work in terms of 10 attributes of a doctor's work. The analysis used the Pearson χ2 test, Spearman's rank correlation coefficient and clustering. Results. The vast majority of doctors admitted that their work was interesting (95.9%), but nervous (90.5%) and threatening (77.8%). Nervousness was significantly more often indicated by young doctors. 18.1% of physicians declared their willingness to change their profession. The desire to change profession was most strongly associated with the opinion that work was unpleasant and disgusting. Conclusions. More doctors reported the disadvantages of their work than its advantages. Every fifth declared a willingness to change their profession. The willingness to change profession was strongly related to the overall negative assessment of one's own work. Presumably, as a result of the COVID-19 pandemic, more and more doctors will evaluate their work negatively, which may prompt them to change their profession. This situation requires monitoring the impact of COVID-19 on the workforce and taking remedial measures.